Inorganic reinforced thermoplastic polyester resin composition and molded article made of same
A tailored thermoplastic polyester resin composition with specific components and viscosity control addresses surface defects and burrs in molded products, ensuring high rigidity and appearance without complex mold adjustments.
Patent Information
- Application Number
- JP2021517736
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-05
- Filing Date
- 2020-09-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-09-02
AI Technical Summary
Existing polyester resin compositions with inorganic reinforcing materials face issues such as surface defects, warping, and burrs, especially in thin and long molded products, which affect appearance and rigidity, and require high mold temperatures or complex mold improvements.
A thermoplastic polyester resin composition with specific blending ratios of polybutylene terephthalate, amorphous resin, inorganic reinforcement, ethylene-glycidyl (meth)acrylate copolymer, and transesterification inhibitor, achieving a melt viscosity of 0.5 to 1.5 kPa·s, which suppresses burrs and maintains high rigidity and good appearance.
The composition effectively suppresses burrs and warping while maintaining high strength and rigidity, allowing for improved moldability and appearance in thin-walled, long molded products without the need for high mold temperatures or complex mold improvements.
Smart Images

Figure 0007609063000002 
Figure 0007609063000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic reinforced polyester resin composition containing a thermoplastic polyester resin and an inorganic reinforcing material such as glass fiber, etc. More specifically, the present invention relates to an inorganic reinforced polyester resin composition capable of obtaining molded products having little appearance defects due to floating of the inorganic reinforcing material of the molded product, good surface gloss, little warpage, and very little burrs, even in the case of thin-walled and long molded products, while maintaining high rigidity and high strength. [Background technology]
[0002] In general, polyester resins have excellent mechanical properties, heat resistance, chemical resistance, etc., and are widely used in automobile parts, electric and electronic parts, household goods, etc. In particular, polyester resin compositions reinforced with inorganic reinforcing materials such as glass fibers are known to have dramatically improved rigidity, strength, and heat resistance, and rigidity in particular improves depending on the amount of inorganic reinforcing material added.
[0003] However, if the amount of inorganic reinforcing material such as glass fiber added is large, the inorganic reinforcing material such as glass fiber may come out onto the surface of the molded product, significantly reducing the appearance, particularly the surface gloss, and thus reducing the commercial value.
[0004] Therefore, as a method for improving the appearance of molded products, it has been proposed to set the mold temperature extremely high during molding, for example, at 120°C or higher. However, this method requires special equipment to raise the mold temperature, and not only cannot be used for general-purpose molding with any molding machine, but even when the mold temperature is raised to a high temperature, glass fibers and the like may float at the ends of the molded product that are far from the gate in the mold, making it difficult to obtain a good molded appearance or causing large warpage of the molded product, resulting in defects.
[0005] In recent years, it has been proposed to improve dies so that molded products with high gloss can be obtained from inorganic reinforced materials such as various glass fibers (Patent Documents 1 and 2). The purpose of this mold improvement is to insert highly insulating ceramics, such as zirconia ceramics, into the cavity of the die, control the rapid cooling of the molten resin immediately after it is filled into the cavity, and maintain the resin in the cavity at a high temperature to obtain a molded product with excellent surface properties. However, these methods are expensive to manufacture, and while they are effective for molded products with simple shapes such as flat plates, they have the problem that it is difficult to process ceramics for complex molded products, making it difficult to manufacture a mold with high precision.
[0006] In view of this, polyester resin compositions have been proposed that can suppress the appearance and warpage of molded articles by improving the properties of the resin composition without requiring special improvements to the mold or high temperature settings, even when the resin composition contains inorganic reinforcing materials such as glass fibers (Patent Documents 3 to 6).
[0007] According to the composition of the above-mentioned document, by blending various amorphous resins, copolymer polyesters, etc. and controlling the crystallization behavior of the resin composition, it is possible to obtain a good surface appearance and suppress warpage deformation in a resin composition containing added glass fibers, etc., even when the mold temperature is 100°C or lower.
[0008] On the other hand, in addition to the above-mentioned appearance and warpage, when crystalline resins such as polyester resins are molded, burrs on the molded product may become a problem. When burrs occur, a burr removal process is required, which takes time and costs. In particular, in recent years, for the purpose of weight reduction, the thickness of molded products tends to be thin and the size of molded products tends to be small, so the problem of burrs is relatively frequent. Burrs are caused by mold factors such as gaps that occur due to mold aging, but generally, resin factors have a large influence. It is known that when amorphous resins are used, burrs tend to be reduced due to their viscosity characteristics, but there are not many studies on burrs for crystalline resins other than olefin-based resins that behave similarly to amorphous resins. Of course, there is no description of burrs in the prior art documents described so far, and in polyester resins, there are not many attempts to suppress burrs in terms of composition. In general, burrs tend to occur easily when the fluidity is too good, so it is easy to imagine a method of increasing the viscosity of the resin. However, simply increasing the viscosity requires very high pressure to fill the entire molded product with resin, and the mold may open up due to inability to withstand the pressure, resulting in flash. This tendency is more pronounced when the product is thin. A polyester resin composition that solves this problem has already been proposed (Patent Document 7).
[0009] In recent years, molded products have become longer and longer, and there is a demand for even higher rigidity (flexural modulus of elasticity exceeding 17 GPa). This has resulted in a tendency for the resin filling pressure to become even higher, and the molded product shapes are often prone to burrs. Even for thin-walled, long molded products, there is a demand for materials that have high rigidity and strength, good appearance, and suppress the generation of burrs, and achieving a balance of these qualities has been a very important challenge. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent No. 3421188 [Patent Document 2] Patent No. 3549341 [Patent Document 3] JP 2008-214558 A [Patent Document 4] Patent No. 3390539 [Patent Document 5] JP 2008-120925 A [Patent Document 6] Patent No. 4696476 [Patent Document 7] JP 2013-159732 A Summary of the Invention [Problem to be solved by the invention]
[0011] The objective of the present invention is to provide a polyester resin composition which, in a composition containing an inorganic reinforcing material such as glass fiber, has high strength and high rigidity (flexural modulus of elasticity exceeding 17 GPa) without losing the properties of a polyester resin, while maintaining a good surface appearance, and which is less susceptible to warpage and extremely produces little burrs even in thin-walled, long molded articles. [Means for solving the problem]
[0012] According to the studies made by the present inventors, it has been found that, in an inorganic reinforced thermoplastic polyester resin composition, by adjusting the compounding ratio of polybutylene terephthalate resin, at least one polyester resin other than polybutylene terephthalate resin, and other components, it is possible to achieve both good moldability and a burr suppression effect, even in the case of molding that requires high cycle performance. However, when the rigidity requirement of the material increases (flexural modulus exceeds 17 GPa) and the molded product becomes thinner and longer, it is difficult to maintain the burr suppression effect with the material in the previous invention. Therefore, it was necessary to design a new composition in consideration of the rigidity of the material and the shape of the molded product. As a result of extensive investigations, it was discovered that by adding an amorphous resin to the inorganic reinforced thermoplastic polyester resin composition and by readjusting the compounding ratio of each component, it is possible to effectively suppress burrs even in thin-walled, long molded products that require particularly high rigidity, and this discovery led to the present invention.
[0013] That is, the present invention has the following configuration. [1] A composition comprising: (A) 20-60% by mass of polybutylene terephthalate resin; (B) 5-20% by mass of amorphous resin; (C) 30-60% by mass of inorganic reinforcing material; (D) 0.5-10% by mass of ethylene-glycidyl (meth)acrylate copolymer; and (E) 0.05-2% by mass of an ester exchange inhibitor; and heated at 265°C and a shear rate of 10 sec. -1 1. An inorganic reinforced thermoplastic polyester resin composition, characterized in that the melt viscosity at 0.5 kPa·s or more and 1.5 kPa·s or less. [2] The inorganic reinforced thermoplastic polyester resin composition according to [1], wherein the (B) amorphous resin is at least one selected from the group consisting of polycarbonate resins and polyarylate resins. [3] The inorganic reinforced thermoplastic polyester resin composition according to [1] or [2], characterized in that the inorganic reinforced thermoplastic polyester resin composition has a crystallization temperature upon cooling measured by a differential scanning calorimeter (DSC) of more than 180°C. [4] The inorganic reinforced thermoplastic polyester resin composition according to any one of [1] to [3], wherein the inorganic reinforcing material (C) contains glass fiber and glass flakes. [5] A molded article made of the inorganic reinforced thermoplastic polyester resin composition according to any one of [1] to [4]. Effect of the Invention
[0014] According to the present invention, even in a resin composition containing a large amount of inorganic reinforcing material, the protrusion of the inorganic reinforcing material on the surface of the molded product can be suppressed by adjusting the compounding ratio of each component, so that the appearance of the molded product can be significantly improved, and a molded product with good appearance and low warpage can be obtained while having high strength and high rigidity. Furthermore, even in the case of a thin-walled and long molded product, the generation of burrs due to the pressure during molding can be significantly suppressed, so that a deburring process after molding can be eliminated. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1A is a schematic top view and FIG. 1B is a schematic side view showing an example of a molded product molded for evaluating warpage deformation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will be described in detail below. The blending amount of each component described below represents the amount (mass%) when the inorganic reinforced thermoplastic polyester resin composition is taken as 100 mass%. The blended amount of each component is the content in the inorganic reinforced thermoplastic polyester resin composition, so the blending amount and the content are the same.
[0017] The (A) polybutylene terephthalate resin in the present invention is a resin that is a main component having the highest content among all resins in the inorganic reinforced thermoplastic polyester resin composition of the present invention. The (A) polybutylene terephthalate resin is not particularly limited, but a homopolymer consisting of terephthalic acid and 1,4-butanediol is mainly used. In addition, other components can be copolymerized up to about 5 mol % within a range that does not impair moldability, crystallinity, surface gloss, etc. The copolymerization amount is the amount when the acid component is 100 mol % and the glycol component is 100 mol %. Examples of other components include the components described below.
[0018] Examples of the components to be copolymerized include, as acid components other than terephthalic acid, aromatic or aliphatic polybasic acids such as isophthalic acid, naphthalenedicarboxylic acid, adipic acid, sebacic acid, and trimellitic acid, and esters thereof, and examples of glycol components other than 1,4-butanediol include diethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, ethylene glycol, 1,2-propanediol, 1,3-propanediol, and 2-methyl-1,3-propanediol.
[0019] (A) As a measure of the molecular weight of polybutylene terephthalate resin, the reduced viscosity (a 0.1 g sample is dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured at 30°C using an Ubbelohde viscosity tube; dl / g) is preferably in the range of 0.4 to 1.2 dl / g, more preferably in the range of 0.5 to 0.8 dl / g. If the reduced viscosity is less than 0.4 dl / g, the toughness of the resin decreases and burrs tend to occur due to excessive fluidity, while if it exceeds 1.2 dl / g, burrs also tend to occur more easily due to the large decrease in fluidity.
[0020] The blending amount of (A) polybutylene terephthalate resin is 20 to 60 mass%, preferably 22 to 50 mass%, more preferably 24 to 40 mass%, and further preferably 24 to 35 mass%. By blending the polybutylene terephthalate resin within this range, it becomes possible to satisfy various characteristics.
[0021] The (B) amorphous resin in the present invention may be a known resin such as a polycarbonate resin, a polyarylate resin, a polystyrene resin, an acrylonitrile-styrene copolymer, etc. Considering the compatibility with polybutylene terephthalate resin and the effect of suppressing burrs, a polycarbonate resin and a polyarylate resin are preferred.
[0022] The blending amount of the (B) amorphous resin is 5 to 20% by mass, preferably 6 to 20% by mass, and more preferably 10 to 20% by mass. If it is less than 5% by mass, the effect of suppressing burrs is small, and if it exceeds 20% by mass, it is undesirable because it is likely to cause deterioration of the molding cycle due to a decrease in crystallinity, or a defective appearance due to a decrease in fluidity.
[0023] Polycarbonate resins can be produced by a solvent method, that is, by reacting a dihydric phenol with a carbonate precursor such as phosgene in a solvent such as methylene chloride in the presence of a known acid acceptor or molecular weight modifier, or by transesterification of a dihydric phenol with a carbonate precursor such as diphenyl carbonate. Here, the dihydric phenol preferably used is a bisphenol, particularly 2,2-bis(4-hydroxyphenyl)propane, i.e., bisphenol A. Bisphenol A may be partially or entirely replaced with another dihydric phenol. Examples of dihydric phenols other than bisphenol A include compounds such as hydroquinone, 4,4-dihydroxydiphenyl, and bis(4-hydroxyphenyl)alkane, and halogenated bisphenols such as bis(3,5-dibromo-4-hydroxyphenyl)propane and bis(3,5-dichloro-4-hydroxyphenyl)propane. The polycarbonate may be a homopolymer using one type of dihydric phenol or a copolymer using two or more types of dihydric phenol, or may be a resin copolymerized with a component other than polycarbonate (e.g., a polyester component) within a range that does not impair the effects of the present invention (20 mass% or less).
[0024] Polycarbonate resin has a melt volume rate (unit: cm) measured at 300°C with a load of 1.2 kg. 3A resin having a melt volume rate (m / 10 min) of 1 to 100 is preferably used, and the melt volume rate is more preferably 2 to 80, and further preferably 3 to 40. By using a resin having this range, burrs can be effectively suppressed without impairing moldability. If a resin having a melt volume rate of less than 1 is used, the flowability may be significantly reduced, and moldability may deteriorate. If the melt volume rate exceeds 100, the molecular weight is too low, which may lead to a decrease in physical properties, or problems such as gas generation due to decomposition may easily occur.
[0025] The polyarylate resin may be one produced by a known method. The polyarylate resin may have a melt volume rate (unit: cm) measured at 360° C. under a load of 2.16 kg. 3 A resin having a melt volume rate (m / 10 min) of 1 to 100 is preferably used, and the melt volume rate is more preferably 2 to 80, and further preferably 3 to 40. By using a resin having this range, burrs can be effectively suppressed without impairing moldability. If a resin having a melt volume rate of less than 1 is used, the flowability may be significantly reduced, and moldability may deteriorate. If the melt volume rate exceeds 100, the molecular weight is too low, which may lead to a decrease in physical properties, or problems such as gas generation due to decomposition may easily occur.
[0026] The inorganic reinforcing material (C) in the present invention may include, but is not limited to, plate-like crystal talc, mica, uncalcined clays, calcium carbonate having an unspecified or spherical shape, calcined clay, silica, glass beads, commonly used wollastonite and needle-like wollastonite, glass fiber, scaly glass, carbon fiber, whiskers such as aluminum borate and potassium titanate, milled fiber which is a short glass fiber having an average particle size of about 4 to 20 μm and a cut length of about 35 to 150 μm, etc. Talc and wollastonite are the most excellent in terms of the appearance of the molded product, and glass fiber is the most excellent in terms of strength and rigidity. These inorganic reinforcing materials may be used alone or in combination of two or more types, but it is preferable to use glass fiber mainly in terms of rigidity, etc.
[0027] Among the (C) inorganic reinforcing materials, glass fibers in the form of chopped strands cut to a fiber length of about 1 to 20 mm can be preferably used. Glass fibers with circular and noncircular cross sections can be used as the cross-sectional shape of the glass fibers. Glass fibers with circular cross sections can be very common, with an average fiber diameter of about 4 to 20 μm and a cut length of about 3 to 6 mm. Glass fibers with noncircular cross sections include those that are approximately elliptical, approximately oval, or approximately cocoon-shaped in a cross section perpendicular to the longitudinal direction of the fiber length, and preferably have a flatness of 1.5 to 8. The flatness here is the ratio of major axis / minor axis when a rectangle with the minimum area circumscribing a cross section perpendicular to the longitudinal direction of the glass fiber is assumed, and the length of the long side of this rectangle is the major axis and the length of the short side is the minor axis. The thickness of the glass fibers is not particularly limited, but those with a minor axis of about 1 to 20 μm and a major axis of about 2 to 100 μm can be used.
[0028] These glass fibers can be preferably used after being pretreated with a conventionally known coupling agent such as an organosilane compound, an organotitanium compound, an organoborane compound, or an epoxy compound.
[0029] In the present invention, the blending amount of the inorganic reinforcing material (C) is 30 to 60 mass%, preferably 35 to 60 mass%, and more preferably 35 to 57 mass%. By blending the inorganic reinforcing material within this range, it becomes possible to satisfy various characteristics.
[0030] When talc is used as the inorganic reinforcing material (C), it is important that the amount of talc used is 1% by mass or less in the resin composition, even when used in combination as component (C).Talc acts as a crystal nucleating agent, so if it is used in an amount exceeding this amount, the crystallization speed increases, which is undesirable as it tends to cause poor appearance such as glass lifting.
[0031] When two or more types of inorganic reinforcing material (C) are used in combination in the present invention, a combination of glass fiber and glass flakes can be suitably selected from the viewpoints of flow characteristics and low warpage. By using glass flakes in combination, not only can warpage be suppressed but also flowability can be improved.
[0032] When glass fibers and glass flakes are used in combination as the (C) inorganic reinforcing material, the mass ratio of the glass fibers to the glass flakes is preferably 40:60 to 90:10, and more preferably 45:55 to 80:20.
[0033] When the inorganic reinforced thermoplastic polyester resin composition of the present invention contains 50 to 60 mass % of (C) an inorganic reinforcing material, the flexural modulus of a molded article obtained by injection molding the inorganic reinforced thermoplastic polyester resin composition can exceed 17 GPa.
[0034] The (D) ethylene-glycidyl (meth)acrylate copolymer used in the present invention may be a terpolymer in which ethylene, glycidyl (meth)acrylate, vinyl acetate, acrylic ester, etc. are copolymerized, or a quaternary or higher copolymer. Glycidyl (meth)acrylate refers to either glycidyl acrylate or glycidyl methacrylate. Linear copolymers (random copolymers or block copolymers), graft copolymers, core-shell type polymers, etc. may also be used. The (D) ethylene-glycidyl (meth)acrylate copolymer may be one in which the epoxy groups in the glycidyl (meth)acrylate react during grafting to make the epoxy group residual glycidyl (meth)acrylate component 0 mass%.
[0035] Examples of acrylic acid esters that can be used in the (D) ethylene-glycidyl (meth)acrylate copolymer include (meth)acrylic acid alkyl esters having an alkyl group (which may be linear or branched) with a carbon number of 1 to 22, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, stearyl (meth)acrylate, and methoxyethyl (meth)acrylate, polyalkylene glycol (meth)acrylate esters, alkoxyalkyl (meth)acrylate esters, hydroxyalkyl (meth)acrylate esters, dialkylamino alkyl (meth)acrylate esters, benzyl (meth)acrylate esters, phenoxyalkyl (meth)acrylate esters, isobornyl (meth)acrylate esters, and alkoxysilyl alkyl (meth)acrylate esters. (Meth)acrylamides and (meth)acryl dialkylamides can also be used. These can be used by selecting one or more of them as appropriate.
[0036] The blending amount of (D) ethylene-glycidyl (meth)acrylate copolymer is 0.5 to 10 mass%. Regarding flash, adding a large amount of (D) component improves the viscosity of the entire resin composition and can suppress flash generation during the pressure holding process, but on the other hand, in the case of thin-walled molded products, etc., considerable pressure is applied, which makes the mold open and flash likely to occur, and the fluidity is significantly reduced, which increases the possibility of the molded product's appearance being deteriorated. The blending amount is preferably 0.7 to 8 mass%, more preferably 0.8 to 5 mass%.
[0037] Furthermore, the (D) ethylene-glycidyl (meth)acrylate copolymer can be suitably used in which the glycidyl (meth)acrylate component having residual epoxy groups accounts for 3 to 12 mass% of the entire copolymer. More preferably, it is a copolymer having 3 to 6 mass%. By setting it within the above range, the burr suppression effect can be improved and the toughness of the inorganic reinforced thermoplastic polyester resin composition can also be increased.
[0038] Examples of the ethylene-glycidyl (meth)acrylate copolymer (D) used in the present invention include commercially available products such as Bondfast (manufactured by Sumitomo Chemical Co., Ltd.), Rotader (manufactured by Arkema), Elbaloy (manufactured by Mitsui DuPont Polychemicals), Metablen (manufactured by Mitsubishi Chemical Corporation), and Modiper (manufactured by NOF Corporation).
[0039] The (E) transesterification inhibitor used in the present invention is a stabilizer that prevents transesterification of polyester resins and the like. In alloys of polyester resins, no matter how well the manufacturing conditions are optimized, transesterification occurs to a certain extent due to the addition of heat history. If the degree of reaction becomes very large, the alloy will not be able to provide the expected properties. In particular, transesterification of polybutylene terephthalate resin and polycarbonate resin occurs frequently, so simply alloying these resins is not preferable because the crystallinity of polybutylene terephthalate is greatly reduced. In the present invention, by adding the (E) component, transesterification of polybutylene terephthalate resin (A) and amorphous resin (B) (polycarbonate resin, polyarylate resin, etc.) is prevented, thereby maintaining appropriate crystallinity.
[0040] As the (E) transesterification inhibitor, a phosphorus-based compound having a catalyst deactivation effect for polyester resins can be preferably used, for example, "ADEKA STAB AX-71" manufactured by ADEKA CORPORATION can be used.
[0041] The amount of the (E) transesterification inhibitor is 0.05 to 2% by mass, and more preferably 0.1 to 1% by mass. If it is less than 0.05% by mass, the desired transesterification reaction prevention performance is often not exhibited, and the crystallinity of the inorganic reinforced thermoplastic polyester resin composition may decrease, resulting in a decrease in mechanical properties and poor mold release during injection molding. Conversely, if it is added in excess of 2% by mass, not only is the effect not significantly improved, but it may also be a factor in increasing gas generation.
[0042] The inorganic reinforced thermoplastic polyester resin composition of the present invention can reduce the maximum amount of burrs generated at the flow end to less than 0.20 mm when a long molded product of 150 mm x 20 mm x 3 mmt (thickness) is molded at a cylinder temperature of 275 ° C. and a mold temperature of 110 ° C., and filled for 0.5 seconds with a dwell pressure of 75 MPa. Burrs are usually most often generated when the resin protrudes from the mold due to pressure during the dwell process. This can be improved by adjusting the dwell pressure, but in that case, it may lead to other defects (e.g., sink marks, poor appearance, etc.). On the resin side, it can be improved by adjusting the resin viscosity so that it can withstand the pressure during dwell. However, although the method of increasing the viscosity of the entire resin is effective for burrs during the dwell process, a large amount of pressure is then required when filling the resin, which causes the mold to open during injection, resulting in burrs. This tendency is particularly noticeable in thin-walled molded products.
[0043] Therefore, in order to obtain good molded products without flash in thin-walled molded products, it is ideal to use a resin that has good fluidity during injection (high shear) and whose viscosity increases during the dwelling process (low shear). Examples of resins that exhibit this type of behavior include olefin resins such as polyethylene, and amorphous resins such as acrylic resins. Therefore, it is easy to imagine adding these resins to polyester resins.
[0044] However, when simply adding an olefin resin or an acrylic resin, a relatively large amount needs to be added in order to exhibit ideal behavior, which changes the properties of the resin composition and increases the viscosity of the entire system as described above. However, by blending each component as described above, it has been discovered that the ideal melt viscosity behavior can be expressed without deteriorating the properties of the resin composition, and that flash generation can be suppressed, which is the key point of the present invention.
[0045] The inorganic reinforced thermoplastic polyester resin composition of the present invention preferably has a crystallization temperature at cooling determined by a differential scanning calorimeter (DSC) of more than 180°C. The crystallization temperature at cooling is the top temperature of the crystallization peak of a thermogram obtained by using a differential scanning calorimeter (DSC) to heat up to 300°C at a heating rate of 20°C / min under a nitrogen stream, holding the temperature for 5 minutes, and then cooling down to 100°C at a rate of 10°C / min. If the crystallization temperature at cooling is 180°C or less, the crystallization rate is slow, so that mold release failure due to sticking to the mold or deformation may occur during ejection. The crystallization temperature at cooling is preferably 195°C or less, more preferably 190°C or less.
[0046] In particular, in compositions containing a large amount of inorganic reinforcing material, when the crystallization temperature during cooling exceeds 180°C, the inorganic reinforcing material such as glass fiber is generally noticeable on the surface of the molded product, so-called glass floating is likely to occur. This is because the crystallization speed of the polyester resin composition increases, so the propagation speed of the injection pressure tends to decrease, and part of the inorganic reinforcing material such as glass fiber is exposed on the surface of the molded product. However, the inorganic reinforced thermoplastic polyester resin composition of the present invention has the amount of each component adjusted so that a good appearance can be obtained even at a temperature exceeding 180°C, and it is possible to achieve both good moldability and good appearance.
[0047] In addition, the inorganic reinforced thermoplastic polyester resin composition of the present invention may contain various known additives as necessary within the range that does not impair the characteristics of the present invention. Examples of known additives include colorants such as pigments, release agents, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, plasticizers, modifiers, antistatic agents, flame retardants, dyes, etc. These various additives may be contained in a total amount of up to 5% by mass when the inorganic reinforced thermoplastic polyester resin composition is taken as 100% by mass. In other words, the total amount of the (A), (B), (C), (D) and (E) in the inorganic reinforced thermoplastic polyester resin composition of 100% by mass is preferably 95 to 100% by mass.
[0048] Examples of the release agent include long-chain fatty acids or their esters or metal salts, amide compounds, polyethylene wax, silicone, polyethylene oxide, etc. As the long-chain fatty acids, those having 12 or more carbon atoms are particularly preferred, and examples thereof include stearic acid, 12-hydroxystearic acid, behenic acid, montanic acid, etc., and the carboxylic acid may be partially or entirely esterified with monoglycol or polyglycol, or may form a metal salt. Examples of the amide compounds include ethylene bis terephthalamide, methylene bis stearylamide, etc. These release agents may be used alone or as a mixture.
[0049] The inorganic reinforced thermoplastic polyester resin composition of the present invention was subjected to a test at 265°C and a shear rate of 10 sec -1 The melt viscosity at 200°C is 0.5 kPa·s or more and 1.5 kPa·s or less, preferably 0.6 kPa·s or more and 1.4 kPa·s or less, and more preferably 0.7 kPa·s or more and 1.3 kPa·s or less. If it is less than 0.5 kPa·s, injection molding becomes difficult. On the other hand, if it is more than 1.5 kPa·s, flashing is likely to occur on the molded product.
[0050] The inorganic reinforced thermoplastic polyester resin composition of the present invention can be produced by mixing the above-mentioned components and, if necessary, various stabilizers and pigments, and melt-kneading them. Any method known to those skilled in the art can be used for the melt-kneading method, and a single-screw extruder, a twin-screw extruder, a pressure kneader, a Banbury mixer, etc. can be used. Of these, it is preferable to use a twin-screw extruder. General melt-kneading conditions for a twin-screw extruder are a cylinder temperature of 230 to 300°C and a kneading time of 2 to 15 minutes. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The measured values described in the examples were measured by the following methods.
[0052] (1) Reduced Viscosity of Polybutylene Terephthalate Resin 0.1g of the sample was dissolved in 25ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured at 30℃ using an Ubbelohde viscosity tube (unit: dl / g).
[0053] (2) Amount of burrs The amount of burrs was measured using a microscope when a long molded product of 150 mm x 20 mm x 3 mmt (thickness) was injection molded at a cylinder temperature of 275°C, a mold temperature of 110°C, an injection speed that gave a filling time of 0.5 seconds, and a holding pressure of 75 MPa.
[0054] (3) Appearance of molded product (floating glass fibers, etc.) The appearance of the molded product molded under the above condition (2) was visually observed. ○: No poor appearance due to floating glass fibers on the surface, good △: Some defects in appearance have occurred, especially at the ends of the molded product. ×: Appearance defects occurred throughout the molded product
[0055] (4) Appearance of molded product (grain unevenness) The appearance of the molded product molded under the above condition (2) was visually observed. A mold with a pear-shaped embossing finish with a depth of 15 μm was used. If it was rated "○" or "△", it was at a level that did not pose any particular problems. ○: There is absolutely no appearance defect due to misalignment of the grain on the surface, and it is good. △: A small portion of the molded product has a poor appearance due to the grain being misaligned, and there are some areas that appear white when observed from a different angle. ×: The molded product has a poor appearance due to the overall grain misalignment, and appears white when observed from a different angle.
[0056] (5) Formability When molding was performed under the above condition (2), the cooling time after the end of the injection step was set to 12 seconds, and the mold releasability was evaluated. ◎: No sprue breakage, easy continuous molding, no extrusion pin marks ○: No sprue breakage, etc., and continuous molding is easily possible, but ejection pin marks remain ×: Demolding failure occurs once every shot or once every few shots, and continuous molding is impossible due to sprue removal, etc.
[0057] (6) Melt Viscosity The pelletized resin composition was subjected to a shear rate of 10 sec using a Toyo Seiki Co., Ltd. Capillograph 1B in accordance with ISO 11443, a furnace temperature of 265°C, a capillary [1 mm (inner diameter φ) × 30 mm (length L)], and -1 The melt viscosity was measured.
[0058] (7) Warping Using a film gate mold with a rib on one side and dimensions of 100mm x 100mm x 2mmt (thickness), a molded product with five ribs, each 100mm long, 1mm high and 1mm thick, perpendicular to the resin flow direction was molded in an injection molding machine at a resin temperature of 265-270℃ and mold temperatures of 80℃, 100℃ and 120℃, and the amount of warpage was measured (value A in Figure 1, average value of three molded products). Evaluation was based on the following criteria. ×: Warpage deformation > 3mm △: 3mm ≧ Warpage ≧ 2mm ○: 1.5mm≦warpage amount<2mm ◎: Warpage deformation amount <1.5mm
[0059] (8) Crystallization temperature during cooling A differential scanning calorimeter (DSC) was used, and each sample was sealed in a DSC device in a dry state with a moisture content of 0.03 mass% or less to prevent fluctuations due to moisture. That is, the samples were heated to 300°C at a heating rate of 20°C / min under a nitrogen stream, held at that temperature for 5 minutes, and then cooled to 100°C at a rate of 10°C / min to obtain a thermogram, and the top temperature of the crystallization peak was determined.
[0060] The raw materials used in the examples and comparative examples are as follows. (A) Polybutylene terephthalate resin (A) Polybutylene terephthalate: Toyobo Co., Ltd., reduced viscosity 0.65 dl / g (B) Amorphous resin (B-1) Polycarbonate resin: Sumika Styron Polycarbonate Co., Ltd., "Caliber 301-6", melt volume rate (300°C, load 1.2kg) 6cm 3 / 10min (B-2) Polycarbonate resin: Sumika Styron Polycarbonate Co., Ltd., "Caliber 200-80", melt volume rate (300°C, load 1.2kg) 80cm 3 / 10min (B-3) Polyarylate resin: Unitika Ltd., "U Polymer", melt volume rate (360°C, load 2.16 kg) 4.0 cm 3 / 10min (C) Inorganic reinforcement material (C-1) Glass fiber: Nippon Electric Glass Co., Ltd., "T-120H" (C-2) Flake glass: Nippon Sheet Glass Co., Ltd., "REFG-101" (D) Ethylene-glycidyl (meth)acrylate copolymer (D-1): Ethylene-glycidyl methacrylate-methyl acrylate terpolymer (epoxy group residual glycidyl methacrylate component: 6% by mass), manufactured by Sumitomo Chemical Co., Ltd., "Bondfast 7M" (D-2): Graft copolymer of ethylene-ethyl acrylate copolymer (main chain) and methyl methacrylate-butyl acrylate copolymer (side chain) (epoxy group remaining glycidyl methacrylate component in main chain: 0% by mass), manufactured by NOF Corporation, "Modiper A5300" (E) Esterification inhibitor (E): ADEKA "ADEKA STAB AX-71"
[0061] The inorganic reinforced thermoplastic polyester resin compositions of the Examples and Comparative Examples were prepared by weighing the above raw materials according to the blending ratios (mass%) shown in Table 1, and melt-kneading them in a 35φ twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.) at a cylinder temperature of 270°C and a screw rotation speed of 100 rpm. Raw materials other than component (C) were fed into the twin-screw extruder from a hopper, and component (C) was fed by side feed from a vent port. The pellets of the obtained inorganic reinforced thermoplastic polyester resin composition were dried and then molded into various evaluation samples using an injection molding machine. The molding conditions were a cylinder temperature of 275°C and a mold temperature of 110°C. The evaluation results are shown in Table 1.
[0062] [Table 1]
[0063] As is clear from Table 1, in Examples 1 to 6, by satisfying the ranges specified in the present invention, it is possible to significantly suppress the amount of burrs while maintaining the appearance and moldability of the molded product. Furthermore, in Examples 4 and 5, in which glass fiber and scaly glass were used in combination, the warping suppression effect was large. On the other hand, in Comparative Examples 2 and 3, the (D) component was not included or was below the specified range, so the burr suppression effect was small. In Comparative Example 1, since the (B) component was not included, all of the appearance, warping, and moldability were poor, and in Comparative Example 4, since the (B) component exceeded the specified range, the moldability (mold releasability) was deteriorated. In Comparative Example 5, since the (E) component was not included, the ester exchange reaction proceeded significantly, and the crystallinity was reduced, so the moldability (mold releasability) was deteriorated. Furthermore, in Comparative Example 6, since the melt viscosity was higher than the specified range, the flowability was insufficient, and poor appearance due to floating of the inorganic reinforcing material and uneven graining was observed. [Industrial Applicability]
[0064] According to the present invention, even in resin compositions containing a large amount of inorganic reinforcing material, the protrusion of the inorganic reinforcing material from the surface of the molded product can be suppressed by adjusting the compounding ratio of each component, so that the appearance of the molded product can be greatly improved, and molded products with good appearance and low warpage can be obtained while having high strength and high rigidity. Furthermore, even in thin-walled and long molded products in particular, the generation of burrs due to pressure during molding can be greatly suppressed, so that it is possible to eliminate the need for a deburring process after molding. Therefore, this invention will make a great contribution to the industrial world. [Explanation of symbols]
[0065] L: Flow direction of the resin composition W: perpendicular to the flow of the resin composition 1: Molded product 2: Film Gate 3: Rib A: Warpage deformation amount
Claims
1. (A) 20 to 60 mass% of polybutylene terephthalate resin, (B) 10 to 20 mass% of amorphous resin, (C) 30 to 60 mass% of inorganic reinforcing material, (D) 0.5 to 10 mass% of ethylene-glycidyl (meth)acrylate copolymer, and (E) 0.05 to 2 mass% of an ester exchange inhibitor, wherein the inorganic reinforcing material (C) contains glass fiber and flake glass, and the composition is heated at 265°C at a shear rate of 10 sec. -1 1. An inorganic reinforced thermoplastic polyester resin composition, characterized in that the melt viscosity at 0.5 kPa·s or more and 1.5 kPa·s or less.
2. 2. The inorganic reinforced thermoplastic polyester resin composition according to claim 1, wherein the amorphous resin (B) is at least one selected from the group consisting of polycarbonate resins and polyarylate resins.
3. The inorganic reinforced thermoplastic polyester resin composition according to claim 1 or 2, characterized in that the inorganic reinforced thermoplastic polyester resin composition has a crystallization temperature upon cooling measured by a differential scanning calorimeter (DSC) of more than 180°C.
4. A molded article comprising the inorganic reinforced thermoplastic polyester resin composition according to any one of claims 1 to 3.
Citation Information
Patent Citations
Low warping high surface gloss glass fiber reinforced polyester composite material and preparation method thereof
CN101787183A
Polybutylene terephthalate resin composition
JP2006111693A
Laser welding resin composition and molded product using the same
JP2007269890A
Polybutylene terephthalate resin composition and molding thereof
JP2008120925A
Inorganic-reinforced polyester-based resin composition and method for improving surface appearance of molded product using the same
JP2008214558A